The effect of kenaf core fibre loading on properties of low density polyethylene/thermoplastic sago starch/kenaf core fiber composites - Sarifuddin, Norshahida; Ahmad, Zuraida; Ismail , Hanafi (Penerbit Universiti Sains Malaysia, 2013, 2013)
The rising concern about plastic waste disposal problems and the need for more versatile polymer-based materials has led to an increasing interest on blending synthetic polymer with degradable materials. In this present study, low density polyethylene (LDPE) and plasticised sago starch or so-called thermoplastic sago starch (TPSS) blends containing different percentage of kenaf core fibres (KCF) were prepared. The effects of different fibre loading (10–40% by weight) on the processing and mechanical properties were investigated. In order to further justify the obtained properties, the fabricated composites were characterised by Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC) and water uptake behaviour. In this work, the blend ratio of LDPE/TPSS was fixed at 90/10 (weight percentage) respectively. The results showed that the incorporation of KCF into the blend caused a considerable improvement in tensile strength and Young's modulus. Optimum strength was obtained at 6.704 MPa. FTIR analysis revealed slight changes in band position and intensities due to hydrogen bond formation occurring after the inclusion of fibre. Whereas, decomposition temperature (Td) was improved because of higher thermal stability of fibres and DSC results illustrated the phase compatibility between components in the composite system. Moreover, water uptake tended to increase as the hydrophilic character of KCF impart to the composites.